Cohesiveness and flowability of particulated solid and semi-solid food systems. Issue 10 (15th September 2017) - Tobin, Aarti B.; Heunemann, Peggy; Wemmer, Judith; Stokes, Jason R.; Nicholson, Timothy; Windhab, Erich J.; Fischer, Peter
Abstract : Cohesiveness and flowability of particulated food systems is of particular interest in the oral processing and swallowing of food products, especially for people suffering from dysphagia. Abstract : Cohesiveness and flowability of particulated food systems is of particular interest in the oral processing and swallowing of food products, especially for people suffering from dysphagia. Although cohesiveness of a bolus is an essential parameter in swallowing, a robust technique for objective measurement of cohesiveness of particulated semi- or soft-solids is still lacking. In our approach the ring shear tester is used to measure the cohesiveness and flowability of a model particulated food system based on fresh green pea powders and pastes with controlled moisture content. The focus is on how the cohesiveness and flowability of dry pea particles change as they absorb moisture, swell and soften, while continuously agglomerating until a paste like bolus is achieved. Differently hydrated pea powders start to granulate with increasing moisture content resulting in decreasing flowability and increasing cohesiveness until a critical moisture content of approximately 73 wt% is reached. Above the critical moisture content, cohesiveness starts to decrease and flowability increases, i.e. indicating the transition into the rheological domain of concentrated suspension flow. Besides moisture content we also show that water adsorption capacity i.e. hydration properties and resulting degree of particle softness tremendously influences the flowability factor and cohesiveness of powder systems. Thus ring shear tester can be used to provide guidelines for food paste formulation with controlled cohesiveness.